Restructuring Regional Development Organizations in East Nusa Tenggara Province- Indonesia: A Bureaucratic Reform - Indriyati; Suryono, Agus; Prantiwi, Ratih Nur; Amin , Fadillah (International Journal of Psychosocial Rehabilitation, 2020)
Structuring the regional apparatus organization is one of the patterns of government management in local government organizations, and is a method of dealing with changes in the regulatory environment that occur within the framework of institutional reform. The purpose of this study is to describe, explain and analyze the strategy of implementing regional organizational organization structuring, the process and results of regional corporate organization structuring, the impact of regional organizational organization structuring, and recommending the local regulatory organization structuring model in the Government of East Nusa Tenggara Province. In this study using a qualitative approach to data collection techniques through interviews, observation, and documentation in the Government of East Nusa Tenggara Province. The results show that within the framework of institutional reform, organizational structuring needs to pay attention to strategies, conditions and methods of implementation based on existing conditions and regional needs. This organizational arrangement was carried out with the principle of rightsizing, which is the right function and right size according to Indonesia Government Rules N0. 18 of 2016 concerning Regional Apparatuses.